Metamaterial Based Ku-Band Antenna for Low Earth Orbit Nanosatellite Payload System - Touhidul Alam; Mohammad Tariqul Islam; Mohammad Lutful Hakim; Khalid H. Alharbi; Mandeep Singh Jit Singh; Muntasir M. Sheikh; Rabah W. Aldhaheri; Md. Shabiul Islam; Mohamed S. Soliman (Nanomaterials, 2023)
The concept of nanosatellite technology becomes a viable platform for earth and space observation research to minimize cost and build time for the payload. The communication approach is the essential fundamental attribute of a satellite, of which the antenna is a crucial component for forming a communication link between the nanosatellite and the earth. The nanosatellite antenna must comply with some special requirements like compact size, lightweight, and high gain with a space-compatible structure. This paper proposes a compact metamaterial-based Ku-band antenna with circular polarization for the nanosatellite communication system. The designed antenna obtained an impedance bandwidth of 2.275 GHz with a realized gain of 6.74 dBi and 3 dB axial beamwidth of 165° at 12.10 GHz. The overall antenna size of the designed is 0.51λ × 0.51λ × 0.17λ, which is fabricated on Rogers 5880 substrate material. The antenna results performance has been examined with a 1 U nanosatellite structure and found suitable to integrate with metallic and nonmetallic surfaces of any miniature nanosatellite structure.